Preparation and Release Behavior of Chlorpyrifos Adsolubilized into Layered Zinc Hydroxide Nitrate Intercalated with Dodecylbenzenesulfonate - Liu, Jiexiang; Zhang, Xiaoguang; Zhang, Yongqing (ACS applied materials & interfaces, 2015)
A novel method was developed to make the charge-neutral and poorly water-soluble pesticide chlorpyrifos (CPF) adsolubilize into layered zinc hydroxide nitrate intercalated with dodecylbenzenesulfonate (ZHN-DBS). It included two steps: first, CPF was solubilized into the micelles formed by anionic surfactant sodium dodecylbenzenesulfonate (DBS), nonionic surfactant polyoxyethylene (10) nonyl phenyl ether (TX-10) or zwitterionic surfactant dodecyl betaine (DB), and then ZHN–DBS was poured into CPF micelles to synthesize ZHN–DBS–CPF, ZHN–TX-10–CPF, and ZHN–DB–CPF intercalated compounds. These intercalated compounds were characterized by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetric analysis and differential thermal analysis (TGA/DTA). The results showed that ZHN–DBS–CPF, ZHN–TX-10–CPF, and ZHN–DB–CPF had the basal spacings of 3.29–3.59, 2.57–2.87, and 1.97 nm, respectively, which was discussed from the intercalated mechanism. The intercalated CPF had the higher thermal stability. Release behaviors of CPF from intercalated compounds were investigated and analyzed in buffer solutions (pH 5.0 and 6.8). The results exhibited that the release rates and equilibrium release amounts of CPF were closely dependent on micelles types and release mediums. The release behaviors of ZHN–DBS–CPF and ZHN–TX-10–CPF were well described with pseudo second-order and parabolic diffusion models. The present study suggested that ZHN–DBS–CPF and ZHN–TX-10–CPF could be applied as a potential pesticide delivery system.